2018
DOI: 10.3389/fcvm.2018.00060
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Cardiovascular Disease: Fishing for Causality

Abstract: Cardiovascular disease (CVD) is still the leading cause of death in all western world countries and genetic predisposition in combination with traditional risk factors frequently mediates their manifestation. Genome-wide association (GWA) studies revealed numerous potentially disease modifying genetic loci often including several SNPs and associated genes. However, pure genetic association does not prove direct or indirect relevance of the modifier region on pathogenesis, nor does it define within the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Zebrafish are small (2-4 cm) and show a high fecundity allowing the weekly production of up to 300 eggs per breeding pair. The externally fertilized eggs develop rapidly, the developing embryos are optically translucent and their development is not completely dependent on the regular function of the cardiovascular system since adequate oxygen supply of all tissues and organs is guaranteed by passive diffusion from the surrounding medium for up to 120 hours postfertilization (hpf) [19,20]. This fact allows the assessment of the role of the loss of known and novel cardiovascular disease genes in vivo that usually results in early embryonic lethality in other animal model systems such as mice.…”
Section: Aspects and Pitfalls During The Early Phase Of Cardiovasculamentioning
confidence: 99%
See 3 more Smart Citations
“…Zebrafish are small (2-4 cm) and show a high fecundity allowing the weekly production of up to 300 eggs per breeding pair. The externally fertilized eggs develop rapidly, the developing embryos are optically translucent and their development is not completely dependent on the regular function of the cardiovascular system since adequate oxygen supply of all tissues and organs is guaranteed by passive diffusion from the surrounding medium for up to 120 hours postfertilization (hpf) [19,20]. This fact allows the assessment of the role of the loss of known and novel cardiovascular disease genes in vivo that usually results in early embryonic lethality in other animal model systems such as mice.…”
Section: Aspects and Pitfalls During The Early Phase Of Cardiovasculamentioning
confidence: 99%
“…Since several years, the zebrafish is used as an attractive model organism to dissect the genetic and molecular underpinnings of cardiovascular development and (patho-)physiology [20,38,39].…”
Section: Modeling Human Cardiovascular Disorders Using the Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two decades the zebrafish has been established as an excellent tool to decipher the genetic as well as molecular underpinnings of various human diseases, including metabolic or cardiovascular disorders [ [4] , [5] , [6] ]. Interestingly, several studies comparing development and function of the endocrine systems demonstrated a high degree of similarity between humans and zebrafish.…”
mentioning
confidence: 99%